Influence of APOE and RNF219 on Behavioral and Cognitive Features of Female Patients Affected by Mild Cognitive Impairment or Alzheimer’s Disease - Mosca, Alessandra; Sperduti, Samantha; Pop, Viorela; Ciavardelli, Domenico; Granzotto, Alberto; Punzi, Miriam; Stuppia, Liborio; Gatta, Valentina; Assogna, Francesca; Banaj, Nerisa; Piras, Fabrizio; Piras, Federica; et al. (Frontiers in Aging Neuroscience, 2018)
The risk for Alzheimer’s disease (AD) is associated with the presence of the ε4 allele of Apolipoprotein E (APOE) gene and, recently, with a novel genetic variant of the RNF219 gene. This study aimed at evaluating interactions between APOE-ε4 and RNF219/G variants in the modulation of behavioural and cognitive features of two large cohorts of patients suffering from Mild Cognitive Impairment (MCI) or AD. We enrolled a total of 306 MCI or AD patients (171 MCI; 135 AD). Subjects were screened with comprehensive neuropsychological evaluations and genotyped for APOE and RNF219 polymorphic variants. Analysis of covariance was performed to assess the main and interaction effects of diagnosis, gender (for APOE only), and genotype on neuropsychological and neuropsychiatric scores. The analysis revealed that compared to APOE- ε4 non-carriers MCI or AD female patients, female MCI or AD carriers of the APOE-ε4 allele show higher levels of anxiety, apathy, irritability, eating disorders, aberrant motor behaviour along with alterations in the total Neuropsychiatric Inventory (NPI) scores. These findings indicate a synergistic effect between gender and the APOE-ε4 allele on the behavioural features of the disease. Also, the simultaneous presence of APOE and RNF219 variants revealed a gender-specific interaction effect on behavioural and cognitive scores. In female MCI patients, RNF219 and APOE variants worked together to negatively impact the levels of anxiety, aberrant motor behaviour, and phonemic verbal fluency. Similarly, in female AD patients, the interaction of the two variants was found to be associated with increased anxiety levels. Our data indicate a novel synergistic activity between gender, APOE, and RNF219 in the modulation of behavioural traits of MCI and AD patients.